Investment of rice farming households in Thailand and Vietnam - Leartlam, Chaniporn; Praneetvatakul, Suwanna; Bunyasiri, Isriya (Kasetsart Journal of Social Sciences, 2021)
Agricultural investment plays an important role in improving production efficiency and income of farmers. However, Thai farmers have lower investment than Vietnam farmers. Study on investment in Thailand is still limited. This paper aims to analyze the factors determining investment in Thailand and Vietnam. Data of 2,414 households in rice farming in Thailand and Vietnam are obtained from TVSEP. The analysis is performed using multinomial logit regression model. Farm households are grouped into 4 categories based on their investment i.e. non-investment, agricultural investment, non-agricultural investment and mixed investment. The results indicated that 40 percent of Thai rice households did not invest and they are those who have low rice planted area and low wealth. By contrast, more than 40 percent of Vietnam rice households invested in agriculture and small scale enterprises (SSEs). Most of them are large farm area and high-income farmers. The result of the econometric analysis revealed that increasing the level of education and financial literacy are significant factors explaining household investment activities in Thailand. For Vietnam, elderly farmers with a lot of experience, enhancing the level of education, increasing in remittances are significant factors stimulating investment. The finding of the study calls for the government to support the farmers’ organizations and their network as well as the idea of large-scale farming and financial knowledge in order to motivate them to invest more in the future.